2021
DOI: 10.3390/ijerph18084035
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nationality on the Psychophysiological Stress Response and Academic Fulfilment in the Final Degree Dissertation

Abstract: The aims of this study were: i. to analyze the effect of nationality on the psychophysiological stress response of physiotherapy last year students in their final degree dissertations; and ii. to analyze the relationship between the stress response and academic results according to nationality. We evaluated the autonomic stress response, cortical arousal, distress subjective perception, and objective and subjective academic fulfilment in Spanish, Italian, and French physiotherapy students during their final de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Values of these temporal domain variables were higher at the pre moment (M1), which reflects a parasympathetic activity closer to a basal state, a fact that contradicts the HR means results. In other research with psychology students, it was found that the HRV parameters sensitive to identify the autonomic modulation were PNN50, RMSSD, SD1, SD2, and HF [18], and with physiotherapy students, the sensitive parameters were PNN50, RMSSD, SD1 and SD2 [19]. With athletes' sample, PNN50, RMSSD, and HF were the parameters sensitive to identify the autonomic modulation [20], and with military population the parameters were RRSD, and RR interval mean [21].…”
Section: Discussionmentioning
confidence: 90%
“…Values of these temporal domain variables were higher at the pre moment (M1), which reflects a parasympathetic activity closer to a basal state, a fact that contradicts the HR means results. In other research with psychology students, it was found that the HRV parameters sensitive to identify the autonomic modulation were PNN50, RMSSD, SD1, SD2, and HF [18], and with physiotherapy students, the sensitive parameters were PNN50, RMSSD, SD1 and SD2 [19]. With athletes' sample, PNN50, RMSSD, and HF were the parameters sensitive to identify the autonomic modulation [20], and with military population the parameters were RRSD, and RR interval mean [21].…”
Section: Discussionmentioning
confidence: 90%
“…Other studies regarding physiotherapy students during their bachelor's thesis showed how sympathetic nervous system modulation remained high throughout the defense, showing low HRV values [5,6]. However, another study about the impact of nationality on the psychophysiological stress response in the bachelor's thesis indicated that the Spanish student group showed greater parasympathetic activity from the beginning to the end of the defense, compared to the French and Italian student groups [4].…”
Section: Discussionmentioning
confidence: 98%
“…This new education model is integrated in the new European Higher Education Area Space (HEAS), which establishes a bachelor's thesis as a requirement for obtaining the bachelor's degree. The bachelor's thesis allows students to acquire basic research abilities, providing knowledge about scientific methods and their applications, before they finally 2 of 11 defend the project in a public defense before a court of professors [4][5][6]. University students consider the bachelor's thesis as the single-most cognitively demanding work at university, describing their feelings of anxiety and uncertainty [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticipatory anxiety response is a normal response, presenting an adaptive function since it prepares the organic systems (both physiologically and psychologically) to deal with a potential threat [ 1 ]. This organic response has also been evaluated in both military [ 51 , 52 ], and civil contexts where the level of contextual demand or stress is higher, such as commercial pilots [ 53 , 54 ], sports competitions [ 55 , 56 ], sanitary [ 49 , 50 ], or even academic events [ 57 , 58 , 59 ]. In this line, we should point out that the first incidence occurred only in the first take-off for all subjects, which is a source of additional stress to this anticipatory response [ 3 ], explaining this greater sympathetic modulation of the participants.…”
Section: Discussionmentioning
confidence: 99%